Writing competence of junior high school students at two junior high schools in Yogyakarta - Ayah Ahmed Zidan (Journal of English Language and Pedagogy, 2020)
The problem limitation in this research is only about English writing competence in junior school and only compare two schools in Yogyakarta, that are MTs Negeri 1 Bantul and SMPN 1 Pengasih. To describe the student writing competencies at two junior high schools. The objectives of this study are to reveal the factors affecting the students writing competencies and to find out the solution to overcome the problem in writing competencies. In collecting data, the researcher used documentation technique. This technique was implemented by making use of teachers’ collection of the students’ writing tasks. Based on the result and analysis, so the conclusion in this research as follows the writing competencies of the ninth grade students of two junior high schools are at good enough level. The factors affecting the students English writing competencies are their ability, the learning process and classroom situation. When the students weak in grammar, they have to make practice more, and also when they got in doing the difficult assignment. When the step of rhetoric weak, so the students must more practise in daily life, also for the make clarity of meaning and the relationship between ideas can improve by more practice in daily life, they can use the English language. About the weak vocabulary, so the teacher can practice and give more homework about the vocabulary and the task for example in writing and reading a lot of procedure text or story. The solution to overcome the problem in writing competencies such as make a lot of training or practice English in daily life, the teachers should employ active learning to support students engaged in teaching-learning process